(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2023)
In one of the lathes (TACCHI FTC 100) used in the central workshop of the Libyan Iron and Steel Company, a number of bearings are used to support all the pieces to be turned. In this research, we tried to study the stresses arising in the bearings used in this lathe and the extent of their responsibility for the failure of the bearing, and the total deformation of the bearing under loading conditions was examined by using finite element analysis . Through the analysis, it became clear that the maximum resulting stresses in the bearings (2.68673×107N/M2 ) did not exceed the yield stress of the bearing material (Chromium Stainless Steel 100 Cr6), and also did not produce significant deformations in the bearings (only 0.0376373 mm ) , and this means that the resulting stresses were not the cause of the bearings failure, which is likely to occur for other reasons.